Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices - Strauß, Sara (anglistik & englischunterricht)

Facets of Children’s Fears in Twentieth- and Twenty-First-Century Stream-of-Consciousness Fiction - Strauß, Sara (Who’s afraid of...? Facets of Fear in Anglophone Literature and Film)

Constructions of ‘Otherness’ in Frances Hodgson Burnett’s The Secret Garden - Strauß, Sara (A Hundred Years of The Secret Garden – Frances Hodgson Burnett’s Children’s Classic Revisited)

The Persistence of Modernism in Light (Critical Engagements: A Journal of Criticism and Theory: Special Section: Eva Figes)

Der Zauber Magischer Welten - Flotmann, Christina
Interview 11 Oct. 2012

Frequency tuning of piezoelectric energy harvesters by magnetic force - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Smart Materials and Structures)
A piezoelectric energy harvester is an electromechanical device that converts ambient mechanical vibration into electric power. Most existing vibration energy harvesting devices operate effectively at a single frequency only, dictated by the design of the device. This frequency must match the frequency of the host structure vibration. However, real world structural vibrations rarely have a specific constant frequency. Therefore, piezoelectric harvesters that generate usable power across a range of exciting frequencies are required to make this technology commercially viable. Currently known harvester tuning techniques have many limitations, in particular they miss the ability to work during harvester operation and most often cannot perform a precise tuning. This paper describes the design and testing of a vibration energy harvester with tunable resonance frequency, wherein the tuning is accomplished by changing the attraction force between two permanent magnets by adjusting the distance between the magnets. This tuning technique allows the natural frequency to be manipulated before and during operation of the harvester. Furthermore the paper presents a physical description of the frequency tuning effect. The experimental results achieved with a piezoelectric bimorph fit the calculated results very well. The calculation and experimental results show that using this tuning technique the natural frequency of the harvester can be varied efficiently within a wide range: in the test setup, the natural frequency of the piezoelectric bimorph could be increased by more than 70%.

Analytical determination of characteristic frequencies and equivalent circuit parameters of a piezoelectric bimorph - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric structures are nowadays used in many different applications. A better understanding of the influence of material properties and geometrical design on the performance of these structures helps to develop piezoelectric structures specifically designed for their application. Different equivalent circuits have been introduced in the literature to investigate the behaviour of piezoelectric transducers. The model parameters are usually determined from measurements covering the characteristic frequencies of the piezoelectric transducer. This article introduces an analytical technique for calculating the mechanical and electrical equivalent system parameters and characteristic frequencies based on material properties and geometry for a cantilever bimorph structure. The model is validated by measurements using a cantilever bimorph and fits the experimental results better than previous models. The model gives a full set of piezoelectric transducer parameters and is therefore well suited for further theoretical investigations of piezoelectric transducers for different applications. The results also show that even small manufacturing tolerances have a considerable effect on the system parameters and characteristic frequencies. This might lead to intolerable deviations, especially in dynamic applications and should be avoided by careful design and production.

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

An efficient simulation technique for high-frequency piezoelectric inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Ultrasonics Symposium (IUS), 2012 IEEE International)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. These motors can operate in ``stick-slip'' or ``slip-slip'' mode, with the fundamental frequency of the driving signal ranging from several Hertz to more than 100 kHz. To predict the motor characteristics, a Coulomb friction model is sufficient in many cases, but numerical simulation requires microscopic time steps. This contribution proposes a much faster simulation technique using one evaluation per period of the excitation signal. The proposed technique produces results very close to those of timestep simulation for ultrasonics inertia motors and allows direct determination of the steady-state velocity of an inertia motor from the motion profile of the driving part. Thus it is a useful simulation technique which can be applied in both analysis and design of inertia motors, especially for parameter studies and optimisation.
Keywords: friction; ultrasonic motors; Coulomb friction model; efficient simulation technique; friction contact; high-frequency piezoelectric inertia motor; motor characteristics prediction; numerical simulation; slip-slip mode; stick-slip mode; time-step simulation; ultrasonic inertia motor; Acceleration; Acoustics; Actuators; Computational modeling; Friction; Numerical models; Steady-state

Synthesis of piezoelectric materials by ultrasonic assisted hydrothermal method - Isobe, Gaku; Ageba, Ryo; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (AIP Conference Proceedings)
Hydrothermal method enables to synthesize high quality piezoelectric materials. To shorten the reaction time and to get higher quality materials, we propose an ultrasonic irradiation to the solution during the hydrothermal method. We named it ultrasonic assisted hydrothermal method (UAHTM). We have synthesized lead-free piezoelectric material and PZT thin film and the effect of UAHTM have been confirmed. In this study, we tried to improve UAHTM. First, to generate powerful and stable ultrasonic irradiation at high temperature on UAHTM, we developed a new transducer using LiNbO3 single crystal. Second, to prevent contamination to the materials, A Teflon cover on the tip of transducer was attached.
Keywords: contamination; lead compounds; piezoelectric materials; piezoelectric thin films; piezoelectric transducers; ultrasonic effects

Probabilistic Planning for Predictive Condition Monitoring and Adaptation Within the Self-Optimizing Energy Management of an Autonomous Railway Vehicle - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph (Journal of Robotics and Mechatronics)
Self-optimizing mechatronic systems are a new class of technical systems. On the one hand, new challenges regarding dependability arise from their additional complexity and adaptivity. On the other hand, their abilities enable new concepts and methods to improve the dependability of mechatronic systems. This paper introduces a multi-level dependability concept for selfoptimizing mechatronic systems and shows how probabilistic planning can be used to improve the availability and reliability of systems in the operating phase. The general idea to improve the availability of autonomous systems by applying probabilistic planning methods to avoid energy shortages is exemplified on the example of an innovative railway vehicle.
Keywords: self-optimizing systems; dependability; probabilistic planning; energy management

Benteler Vehicle Dynamics -- Fahrdynamikentwicklung basierend auf einer neuen Auslegungstheorie - Kohl, Sergej; Sextro, Walter; Zuber, Armin (8. Tag des Fahrwerks, Aachen, 2012)

Piezoelectric applications of hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics - Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
A hydrothermal method utilizes a crystallization process in the solution so that the pure and high-quality powders can be realized. Sintering from the hydrothermal KNbO3 and NaNbO3 powders, a high-dense lead-free piezoelectric (K,Na)NbO3 ceramics could be obtained (density: 98.8%). Concerning about the g33 constant, high value as large as commercial PZT ceramics was measured. Therefore, the hydrothermal (K,Na)NbO3 ceramics is usable for the sensors and the energy harvesting devices. To demonstrate the (K,Na)NbO3 ceramics, a hydrophone sensor was fabricated and evaluated.
Keywords: crystallisation; hydrophones; piezoceramics; potassium compounds; powder technology; powders; sensors; sintering; sodium compounds; (K0.48Na0.52)NbO3; KNbO3 powder; NaNbO3 powder; crystallization; energy harvesting devices; g33 constant; hydrophone sensor; hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics; hydrothermal method; piezoelectric applications; sintering; Materials; Transducers

Piezoelectric Properties of Li-Doped (K0.48Na0.52)NbO3 Ceramics Synthesized Using Hydrothermally-Derived KNbO3 and NaNbO3 Fine Powders - Maeda, Takafumi; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
[$Li_x(Na_0.52K_0.48)_1-x]NbO_3 (0 ≤ x ≤ 0.091)$ ceramics were synthesized using hydrothermal powders and the lithium doping content was controlled to optimize their piezoelectric properties. The raw KNbO$_3$ and NaNbO$_3$ powders were obtained separately by a hydrothermal method and LiNbO$_3$ powders were prepared by milling a commercial LiNbO$_3$ single crystal. These powders were mixed with ethanol at a molar ratio LiNbO$_3$: ($Na_0.52K_0.48$)NbO$_3 = x : 1-x$. The synthesized powders were sintered at 1060--1120 $\,^{°}$C for 2 h. We succeeded in obtaining highly dense [$Li_x(Na_0.52K_0.48)_1-x]NbO_3$ ceramics using hydrothermal powder. The X-ray diffraction patterns revealed that the crystal phase changed from orthorhombic to tetragonal at around x = 0.06. At this morphotropic phase boundary (MPB), the c/a ratio changed from 1.016 to 1.024 and the highest piezoelectric constant was obtained with the chemical component of [$Li_x(Na_0.52K_0.48)_1-x]NbO_3$. The obtained piezoelectric properties were as follows: $k_33 = 0.51, ε 33^T/ ε _0 = 836$ , $c_33^E = 46$ GPa, $d_33 = 203$ pC/N, and $T_c = 482 $\,^{°}$C$.

Conceptual Design of Advanced Condition Monitoring for a Self-Optimizing System based on its Principle Solution - Sondermann-Wölke , Christoph; Meyer, Tobias; Dorociak, Rafal; Gausemeier, Jürgen; Sextro, Walter (Proceedings of the 11th International Probabilistic Safety Assessment and Management Conference (PSAM11) and The Annual European Safety and Reliability Conference (ESREL2012))
The rapid development of communication and information technology opens up fascinating perspectives, which go far beyond the state of the art in mechatronics: mechatronic systems with inherent partial intelligence. These so called self-optimizing systems adapt their objectives and behavior autonomously and flexibly to changing operating conditions. On the one hand, securing the dependability of such systems is challenging due to their complexity and non-deterministic behavior. On the other hand, self-optimization can be used to increase the dependability of the system during its operation. However, it has to be ensured, that the self-optimization works dependable itself. To cope with these challenges, the multi-level dependability concept was developed. It enables predictive condition monitoring, influences the objectives of the system and determines suitable means to improve the system's dependability during its operation. In this contribution we introduce a procedure for the conceptual design of an advanced condition monitoring based on the system's principle solution. The principle solution describes the principal operation mode of the system and its desired behavior. It is modeled using the specification technique for the domain-spanning description of the principle solution of a self-optimizing system and consists of a coherent system of eight partial models (e.g. requirements, active structure, system of objectives, behavior, etc.). The partial models are analyzed separately in order to derive the components of the multi-level dependability concept. In particular, the reliability analysis of the partial model active structure is performed to identify the system elements to be monitored and parameters to be measured. The principle solution is extended accordingly: e.g. with system elements required for the realization of the dependability concept. The advantages of the method are shown on the self-optimizing guidance module of a railroad vehicle.
Keywords: Mechatronic Systems; Principle Solution; Condition Monitoring; Conceptual Design

Analysis of different operation modes for inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (ACTUATOR 2012 Conference Proceedings)
Piezoelectric inertia motors, also known as ``stick-slip-drives'', use the inertia of a body to drive it by means of a friction contact in small steps. While these steps normally involve stiction and sliding, the motors can also operate in ``slip-slip'' mode without any phase of static friction. In this contribution, a one degree of freedom model of an inertia motor driven by an ideal actuator is analysed. Start-up and constant velocity operation of the motor are investigated and appropriate quantities to compare ``stick-slip'' and ``slip-slip'' operation are determined. Different aspects such as velocity, uniformity of motion, load capacity, robustness, efficiency, and wear are considered. The analysis allows both modes to be applied advantageously in different applications and can widen the field of application of piezoelectric inertia motors. Motor designers are enabled to choose the appropriate mode of operation and the best drive parameters for their individual applications.
Keywords: Piezoelectric Inertia Motors; Drive Signals; Stick-slip; Slip-slip

Biomimetic approaches to create anti-reflection glass surfaces for solar cells using self-organizing techniques - Achtelik, J.; Sievers, W.; Lindner, Jörg (Materials Science and Engineering: B)
Aiming to diminish the reflection losses of glass covered light harvesting devices, the optical reflectivity of nanostructured glass surfaces is studied theoretically and experimentally. The work is inspired by the nanoscale roughness of insect eyes, which is tried to be replicated on a technical glass surface. To this end, the reflectivity of glass surfaces with topographies represented by linear, parabolic and Fermishaped glass/air fill factor profiles is calculated for normal incidence. It is shown that using the latter ones, an almost complete suppression of reflections can be achieved. A simple, self-organization technique to create such Fermi-shaped filling factor profiles in glass experimentally is also presented.

Growth of cubic GaN on 3C–SiC/Si (001) nanostructures - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Duschik, K.; Niendorf, T.; Maier, H.J.; Meertens, D.; Tillmann, K.; As, D.J.; Lindner, Jörg (Journal of Crystal Growth)
We report on the molecular beam epitaxy growth of cubic GaN on 3C–SiC (001) nanostructures. Transmission electron microscopy (TEM) studies show phase-pure cubic GaN crystals with a low defect density on top of the post shaped 3C–SiC nanostructures and GaN grown on their sidewalls, which is dominated by {111} planar defects. The nanostructures, aligned parallel and perpendicular to the [110] directions of the substrate, are located in anti-phase domains of the 3C–SiC/Si (001) substrate. These anti-phase domains strongly influence the optimum growth of GaN layers in these regions. TEM measurements demonstrate a different stacking fault density in the cubic GaN epilayer in these areas.

Self-Organized Nanostructure Formation for Anti-Reflection Glass Surfaces - Achtelik, Jörn; Kemper, Ricarda M.; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
Two methods to create biomimetic anti-reflection nanostructures in ordinary glass microscope object slides are presented. One technique is based on a nanosphere lithography process combined with physical vapour deposition of nickel and reactive ion etching (RIE). The other uses plasma induced dewetting of a smooth nickel surface. The amount of reflected light was measured and a method to simulate the reflectivity from an atomic force microscopy (AFM) topography scan of the glass surface is presented. The reflectivity for visible light at normal incidence was reduced to 20-50 % of the original value with both methods and the simulation gives results in good agreement to the measurement.

Gyrotropic Metamaterials - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg